From polymer matrix to cell structure: STG/TEMs/PU energy-absorbing foamed composites with strain rate-dependent and bimodal cellular structure - Xiaoke Liu; Kejing Yu; Pengwan Chen (Materials & Design)
In this study, based on polyurethane (PU) foam material, intelligent macromolecular material “shear thickening gel (STG)” with strain rate-dependent characteristic was chosen as the reinforcing material to strengthen the PU matrix, and water together with thermal expansion microspheres (TEMs) were used as double foaming agents to prepare STG/TEMs/PU foamed composites with bimodal cell structure and excellent mechanical properties. We examined the effects of varying STG and TEMs contents on the cell structure and investigated the contributions of the matrix material and cell structure to the strain rate-dependent properties. The results demonstrate that incorporating STG into the matrix is more beneficial for enhancing the strain rate-dependent behavior of the foamed composites than altering the cell structure. Moreover, loading-unloading test analyses revealed that STG-reinforced foam and TEMs-reinforced foam exhibit distinct softening and hysteresis behaviors. This finding not only enhances our understanding of the mechanisms by which STG and TEMs operate in PU foams but also establishes a foundation for improving the performance of these materials under various extreme application conditions. Finally, we elucidated the energy dissipation mechanism of STG/TEMs/PU foam composites under multi-cycle compression loads, providing clearer insights into the microscopic changes occurring within the materials.